Heating cells in acid methanol for 30 min without freeze-drying provides adequate yields of fatty acids and alcohols for gas chromatographic characterization of mycobacteria. - Jimenez, J (1986)
We studied the release of mycobacterial fatty acids (as methyl esters) and secondary alcohols after heating both wet and freeze-dried cells in methanolic hydrogen chloride for different time periods. A 30-min heating of the mycobacteria without prior freeze-drying was found adequate in a routine gas chromatographic procedure for strain and species characterization.